Dynamic Assessment of Thailand's Available Transfer Capability for Third-Party Access - Dhamrongsak Khakkharho; Thanakorn Sutheerawut; Junlachat Sanjaisue; Thongchart Kerdphol; N. Teera-achariyakul; Tossaporn Surinkaew; Watcharakorn Pinthurat (My University, 2024)
Thailand is experiencing significant growth in renewable energy sources, such as solar power and wind power. This growth is leading to an increase in independent electricity trading across public, private, and household sectors, making Thailand the origin of third-party access to electricity in the country. However, the current transmission infrastructure is struggling to keep pace with this development, making it challenging to assess regional transmission capabilities accurately. Furthermore, the rapid urban and industrial growth has also resulted in a significant increase in electricity demand, emphasizing the urgent need for a robust transmission and distribution network. To address these challenges, a paper is currently underway to model the remaining transmission capacity in Thailand's regions using real data and sophisticated electrical engineering software. This analysis primarily concentrates on Available Transfer Capability known as ATC, which draws insights from various methods used in the Indian case study. The goal is to enhance the utilization of the transmission system, support independent electricity trading, and guarantee the stability, security, and reliability of the power system in line with the changing electricity market.
Keywords: Healthcare Policy and Management; Public-Private Partnership Projects